Beltraniomyces, a new genus of Dematiaceous Hyphomycetes from India - and N. KRISHNA RAO, C. MANOHARACHARY*, D.K. AGARWAL (Indian Phytopathology, 2003)
An interesting anamorphic genus Beltraniomyces gen. novo is illustrated and described from India. The genus is characterized by the absence of stroma, setae and hyphopodia, having macronematous, mononematous conidiophores producing symmetrically biconic conidia without a beak and is compared with the allied genera Beltrania, Beltraniella, Beltraniopsis, Pseudobeltrania and Ellisiopsis.